Digging out the biology properties of tRNA-derived small RNA from black hole - Shi, Hengmei; Xie, Jiaheng; Pei, Shengbin; He, Danni; Hou, Huyang; Xu, Shipeng; Fu, Ziyi; Shi, Xiaoyan (Frontiers in Genetics, 2023)
An unique subclass of functional non-coding RNAs generated by transfer RNA (tRNA) under stress circumstancescir-cumstances is known as tRNAtransfer RNA (tRNA)-derived small RNARNAs (tsRNA)(tsRNAs). tsRNAs can be dividedseparated into tRNA halves and tRNA-derived fragments (tRFs) based on the different cleavage sites. Like microRNAs, tsRNAs can attach to Argonaute (AGO) proteinsAGO protein to target downstream mRNA in a base pairing manner, which plays a role in rRNA processingribosome biosynthesis, gene silencing, protein expression and viral infectionreverse transcription. Notably, tsRNAs can also directly bind to proteinproteins and exhibit functions in transcription, protein modificationpost-transcriptional modification, gene expression, protein stabilization, and signaling pathways. tsRNAs can control the expression of tumor suppressor genes and participate in the initiation of cancer. It can also mediate the progression of diseases by regulating cell viability, migration ability, inflammatory factor content and autophagy ability. Precision medicine targeting tsRNAs and drug therapy of plant-derived tsRNAs are expected to be used in clinical practice. In addition, liquid biopsy technology based on tsRNAs indicates a new direction for the non-invasive diagnosis of diseases.